Discovery in Student-Centered Learning: The Essential Role in Guiding Students' Mathematical Reasoning and Proof - Scristia; Herman, Tatang (International Journal of Research in Mathematics Education, 2025)
This study explores how a teacher focuses students' mathematical reasoning to advance instruction through the implementation of five mathematically productive teaching streams: guidance to student reasoning and proof, student mathematical discussion, working with selected student mathematical arguments, working with worksheets on the proof process. The findings suggest that discovery teaching, especially guidance to students reasoning and proof resulted in the implementation of teaching discovery in student-centered learning. This teaching highlights whose mathematics is centered in the classroom and whether the focus is on correct answers and procedures or on students' mathematical thinking and justification.